Kontekstualisasi Pilkada Riau: Sosiokultural, Relasi Klientalistik dan Indikasi Politik Uang - Misra, Fauzan; Sudarmoko, Sudarmoko; Apriwan, Apriwan; Hakim, Amri; Ichsan Kabullah, Muhammad; Rahman, Fajri (Komisi Pemberantasan Korupsi, 2021)
The local election as an electoral competition cannot be separated from the threat of money politics. This study tries to identify the amount of money politics received by voters in the Pemilukada. This is important considering that there are no clear parameters in calculating the real costs incurred by candidates in the Pemilukada. The results of the study indicate that sociocultural factors play an important role in the local elections in Riau. This study also found that there are three types of clientelistic relationships that are built, namely ethnicity-based relationships, broker-based relationships, and constituent service-based relationships.